Malaysian English language novice teachers’ challenges and support during initial years of teaching - Vishin Nair Chandran; Intan Safinas Mohd Ariff Albakri; Siti Shuhaida Shukor; Noriah Ismail; Mohd Haniff Mohd Tahir; Mazlin Mohamed Mokhtar; Noraini Zulkepli (Universitas Syiah Kuala, 2022)
This study investigates the challenges encountered by Malaysian English language novice teachers throughout the initial years of their teaching. This study also explores the support received by these novice teachers at the beginning of their careers. The mixed-method research design was adopted for this study. A number of 80 novice teachers participated in the study. Data were collected through a questionnaire survey and an interview with five novice teachers. The findings indicated that the most frequent challenges faced by the novice English language teachers were (1) workload challenges, (2) instructional challenges, and (3) social status and identity challenges. The results also showed that the most frequent support received by the novice teachers was collegial support. Based on the findings, one of the most crucial issues to be addressed during the teacher training was equipping the novice teachers with the knowledge and skill in managing their multiple work and responsibilities in schools. Training novice teachers in using various instructional methods, particularly on the use of computer technology is also important. The novice teachers also need to be provided with more professional development courses that can develop their confidence in teaching, help them build a relationship with students and colleagues, and educate them on how to manage their problematic learners. A structured support system with good mentoring practices during the initial years of teaching is also crucial in assisting the novice teachers to adapt to the teaching environment and carry out assigned responsibilities.